2017
DOI: 10.5114/aoms.2017.67284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adenosine receptor antagonists in MPTP mouse model of Parkinson’s disease: mitochondrial DNA integrity

Abstract: IntroductionIn Parkinson’s disease (PD), compelling data indicate a functional link between adenosine/dopamine receptors and the progression of the neurodegenerative process. The present study was carried out to evaluate the effect of the non-selective adenosine receptor (ADR) antagonist caffeine, as well as the selective antagonists 8-cyclopentyl-1,3-dipropylxanthine (DPCPX), an ADRsA1 antagonist, and ((E)-1,3-diethyl-8-(3,4-dimethoxystyryl)-7-methyl-3,7-dihydro-1H-purine-2,6-dione) (KW-6002), an ADRsA2A anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A 2A R inhibition stopped rotenone-induced motor impairment in a rat model of PD ( Fathalla et al, 2016 ). A 1 as well as A 2A R antagonists were recommended as promising candidates for treatment of PD in a recent paper ( Essawy et al, 2017 ).…”
Section: Disorders Of the Central Nervous System (Cns)mentioning
confidence: 99%
“…A 2A R inhibition stopped rotenone-induced motor impairment in a rat model of PD ( Fathalla et al, 2016 ). A 1 as well as A 2A R antagonists were recommended as promising candidates for treatment of PD in a recent paper ( Essawy et al, 2017 ).…”
Section: Disorders Of the Central Nervous System (Cns)mentioning
confidence: 99%
“…Inhibition or absence of complex I in the respiratory chain causes neuronal apoptosis 18. For example, mitochondrial complex I is inhibited by 1-methyl-4-phenyl-pyridinium, a metabolite of 1-methyl-4-phenyl-1,2,3,6 tetrahydropyridine, which causes cytotoxicity in dopamine neurons 19. Mitochondrial components also show altered function under oxidative stress.…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…[43][44][45] Regarding this, recent studies has demonstrated that caffeine administration increases extracellular dopamine in the striatum in the striatum. 46,47 This indicates that caffeine supplementation may be a potential therapeutic strategy; however, given that maintenance of basal activation of adenosine A1 and A2a receptors plays an important role in antiinflammation, vasodilation, pain modulation, anti-arrhythmia, and metabolic regulation, it is important to understand that the chronic blockage via mega dose (>400 mg per day for adults) of caffeine or pharmacological antagonists against thereceptors may cause several adverse effects.…”
Section: Caffeine Supplementation and Tbimentioning
confidence: 99%